Determinants of Household Education Expenditures by Education Level: The Case of Turkey - KİREN GÜRLER, Özlem; DEMİROGLARI, Sercan (International Journal of Contemporary Economics and Administrative Sciences, 2020)
There is a cost of educational attainment, which is covered by households as well as the state. While government spending on education emphasizes public responsibility for the realization and support of the existing service, education expenditures by households emphasize benefiting from educational services. The expenditures made by households differ by some socio-economic factors and are not the same for all levels of education. Some levels of education may cost more in terms of basic and supportive requirements. The purpose of this study is to identify determinants of household education expendiures and to examine whether education expenditures at education levels are affected by the same determinants. Data used in the study was obtained from the 2017 household budget survey, which was prepared by Turkey Statistical Institute.